083 The impact of the Covid-19 pandemic on neurology outpatients services at Watford General Hospital. Issue 6 (27th May 2022) - Teranaka, Mayu; Mitchell, Harry; Farrell, Krista
Abstract : Objectives: The Covid-19 pandemic has significantly impacted the delivery of outpatient services, and spe- cialists have adjusted to maximise safety for both patients and clinicians. This study examined the impact of remote consultations on the management of neurology outpatients during the Covid-19 pandemic. Method: New neurology referrals to Watford General Hospital from August to September 2020 were reviewed. The type of appointment, telephone or face-to-face (F2F); investigations requested; and outcomes, discharge or follow-up, were analysed. Results: Out of 288 total patients, 59% were triaged to telephone and 41% to face-to-face appoint- ments. Patients with headache (77%; n=78) or suspected seizures (77%; n=61) were more often triaged to telephone appointments. Only 13% and 6% respectively required subsequent review in F2F appoint- ments. Patients were more often triaged to F2F appointments if referred with visual disturbance (80%; n=5), movement disorders (73%; n=30) or weakness (71%; n=17). The discharge rate for telephone (54%) and F2F (53%) groups were similar. Conclusion: This was a retrospective study of referrals to neurology outpatients during the Covid-19 pandemic. Results showed effective triaging with similar outcomes for telephone and F2F appointments. This data suggests that remote consultations are effective and could be helpful in managing patients after the Covid-19 pandemic. mayu.teranaka@nhs.net